Contrasting water use patterns of two important agroforestry tree species in the Mt Elgon region of Uganda. (15th May 2019) - Buyinza, J.; Muthuri, C. W.; Downey, A.; Njoroge, J.; Denton, M. D.; Nuberg, I. K.
ABSTRACT: Lack of information on water use of key agroforestry species is an obstacle to understanding their influence on crop productivity. Cordia africana and Albizia coriaria are the dominant tree species of smallholder farming systems in the Mt Elgon region of Uganda and have multiple uses in agroforestry systems. This study deployed six sap flow meters on stems of three selected trees each of C. africana and A. coriaria on-farm. The objective of the study was to assess the daily water use patterns of these agroforestry tree species at different times of the year. We measured the daily sap flow of these two species using the heat ratio method over a period of 18 months. There was a significant main effect of the interaction between tree species and season on daily water use. The two species show contrasting patterns of seasonal water use across leaf shedding stages characterised by episodes of reverse flow in A. coriaria at specific periods of the year. We propose that reverse flows in A. coriaria were triggered by leaf shading while the zero flows in C. africana, which occurred during rainfall events, could have resulted from a lag phase, an indication that the two species may have different water-use strategies. Although C. africana uses 12–15 l day −1 and A. coriaria uses 20–32 l day −1 based on the study trees, C. africana generally uses 12% more water than A. coriaria on a standardised daily basis. Albizia coriaria exhibited radial variation of sap velocities between the inner and outer thermocouples at different periods of measurement, a phenomenon worth investigating further. The leaf shedding patterns of the two trees provide an opportunity for maximising the temporal complementarities of agroforestry systems where these trees exist. This knowledge of C. africana and A. coriaria tree water use provides critical insight for developing successful long-term tree monitoring and management programs in agroforestry systems.